STUDENTS’ ABILITY IN USING PAST VERBS IN RECOUNT TEXT: A CASE STUDY AT SMPN 1 GUNUNG SARI - Muzhaffar Ramadhan, Imam; Nurtaat, Lalu; Amrullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the ability of eighth-grade students at SMPN 1 Gunung Sari in using past verbs in recount texts. The study was conducted because many students still experience difficulties in applying correct past verb forms when writing about past events. Therefore, the purpose of this research is to identify students’ level of ability in using past verbs in recount texts, to examine the difficulties they face, and to explore the strategies they use to overcome those difficulties. This research employed a descriptive qualitative method. The data were collected through a multiple-choice test as the main instrument, supported by a questionnaire and interviews. The participants of this study were 35 students from class VIII J of SMPN 1 Gunung Sari. The results show that the majority of students have low ability in using past verbs, with 82% of students categorized in the low level, while only 9% are categorized as high ability and 9% as medium ability. The questionnaire results reveal that the main difficulties experienced by students include forgetting the second form of irregular verbs, confusing regular and irregular verbs, and using the present tense instead of the past tense when writing recount texts. Furthermore, the interview results indicate that students try to overcome these difficulties by memorizing verb forms and asking teachers or classmates for help. However, these strategies are still limited and not fully effective in improving students’ grammatical competence. Therefore, more effective and contextualized grammar instruction is needed to help students improve their mastery of past verbs in recount texts.